The development of rainfall temporal pattern in Gombak - Aina Syuhada, Rosnan (2018)
Rainfall temporal pattern analysis of rainfall duration is very important in the process of design rainfall. Information about temporal rainfall distribution within a rainfall event is an important factor that influences hydrological modelling results. Different temporal rainfall distributions can lead to changes in catchment response, and in some cases flooding can occur due to more inconvenient temporal rainfall distribution. In Malaysia, temporal rainfall pattern is provided in Malaysian Urban Storm Water Management Manual Second Edition (MSMA 2). The data available was not updated after 2010 and is stated specific by region. The aim of this study are to develop rainfall temporal pattern in Gombak using Average Variability Method (AVM), Huff Time Distributions Method (HTDM) and Water Resources Research Institute Method (WRRI) and to compare the result for AVM with MSMA 2 and HTDM with WRRI. This study is conducted for seven rainfall stations in Gombak. The data of 5 minutes rainfall interval were extracted and analysed before develop the rainfall temporal pattern based on AVM, HTDM and WRRI method. Based on the comparison between AVM and MSMA 2 made for 7 number of stations at Gombak shows that station 2 which is Ibu Bekalan KM. 16 station for 60 minutes duration has the highest range of percentage difference (1%-79%) and station 5 which is Kg. Kuala Sleh station has the lowest range of percentage difference (6%-19%). For HTDM with WRRI, the result shows that the lowest range is in fourth quartile that is between 0.95% to 13.58. For highest range in differences for 60 minutes duration is in second quartile that is between 24.07% to 32.42%.